Instance Generation from Type Graphs with Arbitrary Multiplicities - Taentzer, Gabriele (Electronic Communications of the EASST, 2012)
Meta modeling is a wide-spread technique to define visual languages, with the UML being the most prominent one. Despite several advantages of meta modeling such as ease of use, the meta modeling approach has a major disadvantage: It does not offer a direct means for generating its language elements. This disadvantage poses a severe limitation on certain applications. For example, when developing model transformations, it is desirable to have enough valid instance models available for large-scale testing. Producing such a large set by hand is tedious. In the related problem of compiler testing, a string grammar together with a simple generation algorithm is typically used to produce words of the language automatically. In this paper, we formalize a restricted form of meta-models by type graphs with multiplicities and introduce instance-generating graph grammars for creating instance graphs representing the abstract syntax structures of models. Thereby, a further step is taken to overcome the main deficit of the meta-modeling approach.